Performance and complications of lumbar puncture in memory clinics: results of the multicenter lumbar puncture feasibility study - Duits, Flora H.; Frölich, Lutz (Alzheimer's and dementia, 2016)
Introduction: Lumbar puncture (LP) is increasingly performed in memory clinics. We investigated patient-acceptance of LP, incidence of and risk factors for post-LP complications in memory clinic populations. Methods: We prospectively enrolled 3868 patients (50% women, age 66 ± 11 years, mini mental state examination 25 ± 5) at 23 memory clinics. We used logistic regression analysis using generalized estimated equations to investigate risk factors for post-LP complications, such as typical postlumbar puncture headache (PLPH) and back pain. Results: A total of 1065 patients (31%) reported post-LP complaints; 589 patients (17%) reported back pain, 649 (19%) headache, of which 296 (9%) reported typical PLPH. Only few patients needed medical intervention: 11 (0.3%) received a blood patch, 23 (0.7%) were hospitalized. The most important risk factor for PLPH was medical history of headache. An atraumatic needle and age >65 years were preventive. Gender, rest after LP, or volume of cerebrospinal fluid had no effect. Discussions: The overall risk of complications is relatively low. If risk factors shown in this study are taken into account, LPs can be safely performed in memory clinics.